Awareness of animal bite and rabies among agricultural workers in rural Dharwad, Karnataka, India - N., Chandan; K., Kotrabasappa (International Journal Of Community Medicine And Public Health, 2016)
Background: Agricultural workers are more vulnerable to animal bites. Rabies is one of the most dangerous and completely preventable diseases. It is most commonly caused by bite of rabid dogs. There are many gaps in the knowledge, attitude and practice with regards to animal bite and rabies. So this study was undertaken to study the knowledge, attitude and practice regarding animal bite and rabies among agricultural workers in rural Dharwad, India. Methods: A cross sectional study was done in rural field practice area of SDMCMSH, Dharwad, India. Data was collected by using pre designed interview schedule from 400 agricultural workers. Data was entered in Epidata v3.1 and analysed using IBM SPSS v20. Descriptive statistics and chi square test were applied. KAP scores were calculated. p<0.05 was considered statistically significant. Results: Average age of study participants was 34.58±13.9 years. 85% were males and 15% females. 88.25% were literates and 11.75% were illiterate. Most of the participants had heard the word rabies (89%). Knowledge score was significantly associated with age and socio economic status. Attitude score was statistically significantly associated with age, religion and socio economic status. Practice score was significantly associated with age, socio economic status and religion. Conclusions: Agricultural workers had fair knowledge about animal bite and rabies. Still there are lot of gaps in knowledge, attitude and practice with respect to prevention and treatment of rabies which have to be addressed by educating them.